Development of MI/SD IPA Curriculum (Analysis of 2013 Curriculum Policy Formulating Patterns) - Safran Safran (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the 2013 curriculum policy for MI/SD. The focus of the study is on developing the science curriculum at the MI/SD level. This research uses a qualitative approach with a descriptive analytical study method based on library research. The use of scientific reference materials is a source of data and